Pengaruh Dana Pihak Ketiga, Non Performing Financing, Capitaladequacy Ratio dan Return on Asset, terhadap Tingkat Likuiditas - Ervina, Ervina; Aridansari, Anindya (Universitas Negeri Semarang, 2016)
Abstract This study aims to determine the effect of variable Third Party Funds, Non Performing Financing, Capital Adequacy Ratio, Return on Assets ratio level of liquidity as measured by the Financing to Deposit Ratio (FDR). This meant that the company engaged in the field of financial services are able to make optimal policy, so that the level of liquidity and the existence of the company is always evolving. Necessary data is secondary data from the monthly financial reports Baitul Maal Wattamwil